Real-time operational feedback: daily discharge rate as a novel hospital efficiency metric. Issue 6 (19th August 2010) - Wong, Hannah J; Wu, Robert C; Caesar, Michael; Abrams, Howard; Morra, Dante
Abstract : Background: Part of delivering quality care means providing it in a timely, efficient manner. Improving the efficiency of care requires measurement. The selection of appropriate indicators that are valid and responsive is crucial to focus improvement initiatives. Indicators of operational efficiency should be conceptually simple, generated in real time, calculated using readily available hospital administrative data, sufficiently granular to reveal detail needed to focus improvement, and correlate with other valid indicators of operational efficiency. Discussion: In this paper, the authors propose daily discharge rate as a novel real-time metric of hospital operational discharge efficiency and compare it with average length of stay. The authors also suggest the use of control charts as an effective way to present daily discharge rate data to clinicians and managers in real time to prompt actionable improvements in discharge efficiency. Conclusion: The authors conclude that daily discharge rate has the potential to drive timely improvements in the discharge process and warrants consideration and further study by others interested in improving hospital operational efficiency and the delivery of quality care.